Consumer acceptance and aroma characterization of navy bean (Phaseolus vulgaris) powders prepared by extrusion and conventional processing methods. (22nd March 2017) - Szczygiel, Edward J; Harte, Janice B; Strasburg, Gale M; Cho, Sungeun
Abstract: BACKGROUND: Food products produced with bean ingredients are gaining in popularity among consumers due to the reported health benefits. Navy bean ( Phaseolus vulgaris ) powder produced through extrusion can be considered as a resource‐efficient alternative to conventional methods, which often involve high water inputs. Therefore, navy bean powders produced with extrusion and conventional methods were assessed for the impact of processing on consumer liking in end‐use products and odor‐active compounds. RESULTS: Consumer acceptance results reveal significant differences in flavor, texture and overall acceptance scores of several products produced with navy bean powder. Crackers produced with extruded navy bean powder received higher hedonic flavor ratings than those produced with commercial navy bean powder ( P < 0.001). GC‐O data showed that the commercial powder produced through conventional processing had much greater contents of several aliphatic aldehydes commonly formed via lipid oxidation, such as hexanal, octanal and nonanal with descriptors of 'grassy', 'nutty', 'fruity', 'dusty', and 'cleaner', compared to the extruded powder. CONCLUSION: Extrusion processed navy bean powders were preferred over commercial powders for certain navy bean powder applications. This is best explained by substantial differences in aroma profiles of the two powders that may have been caused by lipid oxidation. © 2017 Society of Chemical Industry